Bahan Ajar Bangun Datar Berbasis Masalah di Kelas V SD - Rangkuti, Muhammad Zhaky; Sukmawarti, Sukmawarti (JURNAL PENELITIAN PENDIDIKAN MIPA, 2024)
This development research aims to develop problem-based flat shape teaching materials that are suitable for use in the learning process in 5th grader. This research is development research using the ADDIE development procedure which consists of 5 stages. In this research, researchers implemented the ADDIE development model only up to the development stage. The instrument used to collect data was a questionnaire given to several expert validators, namely media expert validators, material expert validators and learning expert validators. From the material expert validation results, a score of 85 was obtained with the criteria "very feasible", from the media expert validator a score was obtained of 87.6 with the criteria "very feasible" and from the learning expert validator a score was obtained of 87.2 with the criteria "very feasible". The average score from the assessment results of the three expert validators was 86.6. Based on the assessment score criteria, it can be said that the problem-based flat shape teaching materials developed are "Very Appropriate" for use in the learning process.